IMPLEMENTATION OF DEVELOPMENT IN SEI PUTIH VILLAGE, KECAMATAN TAPUNG, KAMPAR DISTRICT, 2016 - Rafida Ulfa; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was motivated by the implementation of development in the village of Sei Putih, Tapung Subdistrict, Kampar Regency in 2016 which ran less effectively according to the village musrenbang that had been made by the Village Government. The development in Sei Putih Village is the construction of the TPA building, the construction of the MDA building Nurul Iman, the construction of mosques and mushalla, the construction of the market market for Sei Putih Village, cattle support, livable houses, construction of public buildings, construction of high school buildings, construction of auxiliary health centers, pavement of lotus roads 1, 6 and 7, environmental road lotus 2.3 and 5 as well as village gate construction. The formulation of the problem in this study is why is the development in Sei Putih Village less than optimal?. This study aims to determine the development in Sei Putih Village is less optimal. As a theoretical basis, this research uses the theory of village development from Rahardjo Adisasmita and Village theory from Juliantara. This study uses a qualitative approach, while the type of data research uses qualitative descriptive research. Data collection techniques were carried out by literature study, tracking of official state documents such as Law No. 6 of 2014, Government Regulation No. 43 of 2014, Minister of Home Affairs Regulation No. 113 of 2014, Minister of Home Affairs Regulation No. 114 of 2014 Minister of Village Regulation 2016. Field findings show that the implementation of development in Sei Putih Village, Tapung District, Kampar District has not been optimally realized. This can be seen from the implementation of development in Sei Putih Village, which is still largely abandoned. There are obstacles that make development in Sei Putih Village not optimal. such as the general lack of knowledge of the community on the importance of development, very low community solidarity and ignorance of the community towards village development. Lack of socialization of village government regarding village development is relatively low. Lack of LKMD responsibility for its tasks in development affairs. Sei Putih Village, Supervision of the village government which is still lacking in overseeing the implementation of development in the village of Sei Putih. Keywords: Implementation, Development in the Village, Village